The Role of Gender, Age, and Educational Groups in Utilitarian Motivation For Sharia Products - Marsasi, Endy Gunanto; Barqiah, Sarah (School of Business, IPB University (SB-IPB), 2023)
The development of sharia products continues to increase globally, both in Muslim-majority and minority areas. Diverse cultural backgrounds influence consumers in making choices. Furthermore, there are differences of opinion in previous studies regarding demographic variables. Using functional attitude theory, the gap in consumer motivation from demographic factors in choosing sharia products. The novelty of this study is to emerge from three demographic factors: gender, age, and education level, as fully predicted control variables. Based on this explanation, this study aims to determine the effect of the relationship between the control variables on the utilitarian motivation model in sharia products. Quantitative research was employed on the primary data collected, using the analysis method of multiple group analysis structural equation modelling (SEM) on 362 respondents. The study revealed that control variables (gender, age, educational background) influenced sharia products. The scope of the research is limited, making the results of this study not maximized. In future research, it is expected to be able to expand the scope, use other control variables, and use other related subjects or objects. Keywords: demographic factor, utilitarian motivation, sharia product, intention to use, ideal self-concept